Analisis Pelaksanaan Program Jaminan Kesehatan Nasional (JKN) Penerima Bantuan Iuran (PBI) Di Kota Bengkulu - Lestari, Dwi; Nurdan, Jon Hendri; Theresiana, Yunita (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The National Health Insurance is a program government program that aims to provide certainty of comprehensive health insurance for every Indonesian citizen so that they can live healthy, productive, and prosperous. This study aims to evaluate the implementation of National Health Insurance for Contribution Assistance Recipients in Bengkulu City. This type of research is qualitative. This study uses a qualitative case study approach. The informants for this study were taken as many as 4 people taken by purposive sampling. Data analysis after the researcher finished collecting data in the field using interactive model analysis includes data reduction, data presentation and drawing conclusions. The results of the study found that the evaluation of the implementation of National Health Insurance for Contribution Assistance Recipients in Bengkulu City was quite successful because the context aspect was quite good, the input aspect was good, the process aspect was sufficient and the product aspect was good.